Investigation of important semi-empirical heat transfer models for a natural gas-fueled HCCI engine - Masoud Rabeti (Elsevier, 2021)
Homogeneous charge compression ignition engine is a promising alternative to traditional internal combustion engines mainly due to its high thermal efficiency, low NOx, and soot emissions. Heat transfer from gases to the combustion chamber walls has a significant effect on the combustion, performance, and formation of pollutants in HCCI engines. This study used the zero-dimensional single-zone model coupled with detailed chemical kinetics to compare the accuracy of different semi-empirical heat transfer models In the single-zone model, the heat transfer models including, Annand, Woschni, Hohenberg, Assanis, and Hensel were evaluated in a wide working range of a natural gas-fueled HCCI engine. To the best of the author’s knowledge, the heat transfer has not been experimentally measured in an HCCI engine fueled with natural gas. Therefore, in this investigation, a three-dimensional computational fluid dynamics model with detailed chemical kinetics has been considered to study the heat transfer models. The validation results indicated that the 3D model could accurately estimate the engine-out parameters. Besides, the response surface method was employed to evaluate the impacts of the engine operating parameters, including the intake pressure (1, 1.25, and 1.5 bars), equivalence ratio (0.3, 0.5, and 0.7), and engine speed (800, 1100, and 1400 rpm) on the heat flux as a response factor. The results indicated that Assanis and Hohenberg heat transfer models had the best performance in estimating the heat transfer of an HCCI engine with an average error of 14.3% and 16.3%, respectively, compared with the 3D model.